2014
DOI: 10.1074/jbc.m113.533158
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Mechanism and Mode of Action of the Periplasmic Alginate Epimerase AlgG

Abstract: Background:The alginate epimerase AlgG converts mannuronate to its C5 epimer guluronate at the polymer level. Results: The structure of Pseudomonas syringae AlgG has been determined, and the protein has been functionally characterized. Conclusion: His 319 acts as the catalytic base, whereas Arg 345 neutralizes the negative charge of the carboxylate group during catalysis. Significance: This is the first structural characterization of a periplasmic alginate epimerase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
62
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(63 citation statements)
references
References 85 publications
1
62
0
Order By: Relevance
“…It has further been shown that different R-modules have different binding strength, and that this property influences the degree of processivity displayed by a given epimerase ( Buchinger et al, 2014 ). The structure of P. syringae AlgG was recently published ( Wolfram et al, 2014 ) and AlgG was found to form a long right-handed parallel β-helix similar to that of AlgE4. AlgG was calculated to bind at least nine uronic acid residues.…”
Section: Mannuronan C-5 Epimerasesmentioning
confidence: 93%
See 1 more Smart Citation
“…It has further been shown that different R-modules have different binding strength, and that this property influences the degree of processivity displayed by a given epimerase ( Buchinger et al, 2014 ). The structure of P. syringae AlgG was recently published ( Wolfram et al, 2014 ) and AlgG was found to form a long right-handed parallel β-helix similar to that of AlgE4. AlgG was calculated to bind at least nine uronic acid residues.…”
Section: Mannuronan C-5 Epimerasesmentioning
confidence: 93%
“…The overall structure of both AlgG and the A-module of AlgE4 display structural similarities to some pectate- and pectin lyases of the PL1 family. While the negative charge in the Ca 2+ -dependent pectate lyases and AlgE4 is likely to be shielded by bound calcium, the calcium-independent pectin lyases, and AlgG use an arginine residue ( Vitali et al, 1998 ; Wolfram et al, 2014 ).…”
Section: Mannuronan C-5 Epimerasesmentioning
confidence: 99%
“…After crossing the IM, poly-M is transported through the periplasm, the space between the inner and outer membranes (OM), by a membrane spanning multi-protein machine (Alg44, X, G, K)141617 to the OM protein, AlgE, for secretion181920. In the periplasm, poly-M is modified by O-acetylation (AlgI, J, F and X)212223 and epimerization (AlgG)242526. These modifications add acetyl groups to the C-2 and/or C-3 positions of M residues2122 and convert M residues into G residues2426, respectively.…”
mentioning
confidence: 99%
“…In the periplasm, poly-M is modified by O-acetylation (AlgI, J, F and X)212223 and epimerization (AlgG)242526. These modifications add acetyl groups to the C-2 and/or C-3 positions of M residues2122 and convert M residues into G residues2426, respectively. Both modifications affect polymer composition and its barrier properties against therapeutic intervention and host immunity14272829.…”
mentioning
confidence: 99%
“…As the polymer passages through the periplasm, 22–44% of β ‐1,4‐ d ‐mannuronic acid are converted to α ‐1,4‐ l ‐guluronic acid catalysed by C5‐epimerase AlgG encoded by algG gene to produce alternating d ‐mannuronate and l ‐guluronate blocks and stretches of polymannuronate at polymer level (Wolfram et al . ). Therefore, the algG mutants of P. aeruginosa were found to produce homopolymeric alginate containing only polymeric d ‐mannuronic acid residues (Gimmestad et al .…”
Section: Introductionmentioning
confidence: 97%